Do college students with future work self-salience demonstrate higher levels of career adaptability? From a dual perspective of teachers and students - Lu, Lei; Jia, Qiuhong (Frontiers in Psychology, 2022)
Faced with tremendous employment pressure, how to enhance effective career exploration and career adaptability is crucial for college student's career. This study uses self-assessed data from 840 undergraduate students at three-time points to reveal the formation mechanism of career adaptability from a dual perspective of teacher support and students' effective part-time behavior. In particular, the mediating role of career exploration is introduced based on self-regulation theory, and the moderating role of teacher support and students' effective part-time work is introduced based on social cognitive career theory. The results show that (1) Future work self-salience positively influences career adaptability; (2) future work self-salience indirectly influences career adaptability through career exploration; (3) both teacher support and students' effective part-time behavior positively moderate the indirect relationship between future work self-salience and career adaptability through career exploration. This study attempts to provide practical guidance for college graduates to engage in career exploration and career construction.